Adaptive Administration Technologies of the Service Organizations Staff - Chernysh, Iryna; Kozyk, Mila; Pandzherova, Asya; Szydlo, Joanna (International Journal of Engineering and Technology, 2018)
Administration of human resources is one of the most important components in the management system of a modern enterprise that can repeatedly improve its efficiency, ensure competitiveness and stability. In the globalization context, the administration system in an international company acquires new features, conditioned by the need to effectively operate simultaneously in many countries. In this regard, the experience study of administering human resources in international companies is extremely relevant for Ukrainian enterprises. Personnel administration is impossible without efficient and up-to-date staff of technologies aimed at optimizing personnel in the organization and enhancing efficiency and performance.Â Â Â